Blunt trauma to the extrahepatic biliary tract. A multicenter study. - Pikoulis, Emmanouil; Daskalakis, Panayiotis; Avgerinos, Efthimios D; Gougoudi, Evangelia; Karavokyros, Ioannis; Leppäniemi, Ari; Pavlakis, Emmanouil; Filippou, Dimitrios K; Psalidas, Nikolaos; Condilis, Nicolas; Tsatsoulis, Panayiotis (Ann Ital Chir, 2006)
BACKGROUND/AIMS: Blunt trauma to the extrahepatic biliary tract is a rare and challenging injury The purpose of this paper is to review our experience of these injuries, with special reference to their clinical presentation. PATIENTS AND METHODS: In a retrospective multicenter study of the records of a trauma-admitting in three hospitals, seven patients with blunt extrahepatic biliary tract trauma were identified, one with combined gallbladder and common bile duct injuries and six with a ruptured gallbladder. RESULTS: Except for the patient with the common bile duct injury developing peritoneal signs during observation and being operated 24 hours post-admission, all other patients underwent early laparotomy for shock, peritonitis or positive diagnostic peritoneal lavage (DPL) caused by associated injuries. The common bile duct injury was treated with suture repair over a T tube and the gallbladder injuries with cholecystectomy, except for two cases in which a cholecystostomy was performed. CONCLUSIONS: In patients with blunt trauma, especially to the right upper quadrant, a high index of suspicion and liberal use of diagnostic studies to exclude an isolated extrahepatic biliary tract injury is recommended.
Keywords: Adult; Aged, 80 and over; Bile Ducts, Extrahepatic; Female; Humans; Male; Retrospective Studies; Wounds, Nonpenetrating